Optimization Of Reference Services In The Covid Pandemic At Campus Merdeka Era - Sukartini -; Dewi Puspitasari (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2021)
The COVID-19 pandemic that shook the world in 2020 has forced changes in human life. Humans are forced to find new formulas in their activities. During this COVID-19 pandemic, all activities must continue to be carried out with strict health protocols. During this pandemic, reference services are at the forefront of communication between libraries and users. In this pandemic era, libraries face such massive challenges, so libraries can no longer delay in optimizing reference services. The research method in this paper is literature review or literature study. Researchers will put forward theories about reference services related to the covid pandemic condition and within the framework of an independent campus. Optimization of reference services that can be carried out such Mobile references service; Distance education for users; Ask Librarians; Remote libraries; Research support; Video tutorials; New Flash; Collaboration. The optimization is provide user information in implementing the independent campus program.